Conversion pathways for biomass-derived aviation fuels - Karim, Ahasanul; Islam, Mohammad Amirul; Nayeem, Abdullah; Yousuf, Abu (Elsevier, 2022)
Aviation industry is accountable for discharging a significant amount of carbon dioxide (CO2) in the environment. The sustainable bioenergy sources for the aviation industry are emergent to relieve excessive emission of greenhouse gas and the reliance on conventional petroleum-based fuel. In this context, the renewable aviation fuel could be one of the potential alternatives that can be easily produced from several resources such as oil crops, sugars/starch, waste materials, lignocellulosic biomass, etc. The biomass-derived jet fuels could potentially reduce CO2 emissions in their whole life cycle; thus, they are considered as an attractive replacement of conventional jet fuels. Numerous conversion strategies for biomass into aviation fuels have been found with targeting various categories of feedstocks. To date, several catalytic processes have been implemented to convert biomass-derived oils, alcohols, sugars, and syngas into bio jet fuels. Among them, the aqueous-phase and thermochemical routes have been widely investigated for extracting biomass derived biojet fuels. In this chapter, we have reviewed the four predominant pathways to produce renewable jet fuels including oil-to-jet, alcohols-to-jet, sugar-to-jet, and syngas-to-jet pathways. We have illustrated the conceptual process and addressed the key challenges of pathways in this chapter.